Springback study on leads of quad flat package - Rita Gozali. (2009)
This report presents the study of springback on leads of Quad Flat Package (QFP). One of the factors which affect the forming performance of leads of Quad Flat Package is the springback phenomenon. The amount of springback of QFP copper leads after forming has been studied. An analytical method and a finite element modelling are developed to determine the springback. The results obtained are compared with the experimental measurements. The springback value of closed-form solution compares well with the experimental measurement. When the standard deviation of the measured experimental springback value is taken into consideration, the calculated springback value is within the measured experimental springback population range. The finite element modelling results also correlate relatively well with the experimental measurements.